Baby steps campaign - Chua, Ying Ying (2015)
Baby Steps was a publicity and promotional campaign that focused on the issue of teenage pregnancy. Through raising awareness about the challenges faced by pregnant teenagers, the team aimed to raise willingness of youths to help their pregnant peers. The campaign also aimed to raise awareness of Babes Pregnancy Crisis Support Limited, to improve youth's abilities to help their pregnant peers in times of need. The campaign was shaped by the DAGMAR model and insights from an extensive primary research conducted by the team in October 2014.